PERAN BANK KONVENSIONAL DALAM MENDONGKRAK PEREKONOMIAN DESA PADA PEMBIAYAAN UMKM DALAM KAJIAN EKONOMI SYARIAH - Hasanah, Lutfiatun; Marianingsih, Ita (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
The lack of Sharia economic literacy among rural MSME actors is one of the main reasons for their preference toward loans from conventional banks over Sharia-compliant financing. Limited understanding of the concept of riba (usury), Sharia contractual principles (akad), the easier access to conventional banking services, and the absence of structured Islamic financial education have further reinforced the dependence of MSMEs on interest-based financial systems. This study aims to analyze the level of Sharia economic literacy among rural MSME actors, identify the influencing factors, and formulate strategies to enhance awareness and access to Islamic financing in rural areas. Using a descriptive qualitative approach, this research is expected to contribute to the formulation of educational and inclusive policies that support the transition of MSMEs toward financing systems aligned with Sharia principles.